Long-term efficacy and safety of sapropterin in patients who initiated sapropterin at < 4 years of age with phenylketonuria: results of the 3-year extension of the SPARK open-label, multicentre, randomised phase IIIb trial - Muntau, Ania; Burlina, Alberto; Eyskens, François; Freisinger, Peter; Leuzzi, Vincenzo; Sivri, Hatice Serap; Gramer, Gwendolyn; Pazdírková, Renata; Cleary, Maureen; Lotz-Havla, Amelia S.; Lane, Paul; Alvarez, Ignacio; et al. (Orphanet journal of rare diseases, 2021)
During the initial 26-week SPARK (Safety Paediatric efficAcy phaRmacokinetic with Kuvan®) study, addition of sapropterin dihydrochloride (Kuvan®; a synthetic formulation of the natural cofactor for phenylalanine hydroxylase, tetrahydrobiopterin; BH4), to a phenylalanine (Phe)-restricted diet, led to a significant improvement in Phe tolerance versus a Phe-restricted diet alone in patients aged 0-4 years with BH4-responsive phenylketonuria (PKU) or mild hyperphenylalaninaemia (HPA). Based on these results, the approved indication for sapropterin in Europe was expanded to include patients < 4 years of age. Herein, we present results of the SPARK extension study (NCT01376908), evaluating the long-term safety, dietary Phe tolerance, blood Phe concentrations and neurodevelopmental outcomes in patients < 4 years of age at randomisation, over an additional 36 months of treatment with sapropterin.